Relación entre los objetivos de auditoría y el presupuesto por resultados en el Gobierno Regional de Loreto en el periodo 2024 - Pinedo Usseglio, Joffre Walker (2025)
This research analyzes the relationship between audit objectives and performance-based budgeting in the regional government of Loreto during 2024. The study, with a quantitative approach and correlational design, aimed to determine whether compliance-oriented audits influence the efficiency of budget execution. Surveys were administered to 282 employees, and statistical tests such as Spearman’s correlation revealed a significant positive relationship between the two variables. The results indicate that proper management of audit processes contributes to optimizing the allocation of public resources, ensuring a more transparent and efficient administration. Additionally, it was confirmed that compliance with budgetary regulations and the efficiency of public spending are closely linked to the financial performance of the regional government. The research highlights the importance of audits as a strategic tool to enhance transparency, improve spending efficiency, and achieve institutional goals. These findings provide empirical evidence supporting the need to implement audits that focus not only on control but also on continuous improvement in public management. The study concludes that the synergy between audits and performance-based budgeting is essential for sustainable regional development.